2017
DOI: 10.4025/actasciagron.v39i1.30997
|View full text |Cite
|
Sign up to set email alerts
|

<b>Relationship between manganese toxicity and waterlogging tolerance in <i>Zea mays</i> L. cv. Saracura

Abstract: The objective of this study was to evaluate the relationship between excess manganese and waterlogging tolerance in 18 th selection cycle Zea mays L. cv. Saracura plants. Maize plants were transferred to plastic receptacles containing solutions with different concentrations of manganese. Leaves and roots were evaluated at the beginning of treatment and after 7, 14, and 21 days for chlorophyll content, biomass production and antioxidant metabolism. Mn was strongly translocated from the roots to the leaves, trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This finding is similar to that reported by Rosas et al, (2007) and Inostroza-Blancheteau et al, (2017) in ryegrass from Chilean Andisol. In contrast, recent studies in maize (Silva et al, 2017) and barley genotypes (Huang et al, 2015) showed that some Mn-tolerant genotypes exhibited higher Mn concentrations in shoots than in roots due to internal tolerance mechanisms.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This finding is similar to that reported by Rosas et al, (2007) and Inostroza-Blancheteau et al, (2017) in ryegrass from Chilean Andisol. In contrast, recent studies in maize (Silva et al, 2017) and barley genotypes (Huang et al, 2015) showed that some Mn-tolerant genotypes exhibited higher Mn concentrations in shoots than in roots due to internal tolerance mechanisms.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, Barke, Tatoo and Sebastian showed higher SOD production in roots at increasing Mn doses. This mechanism could be involved in tolerance against oxidative stress, to convert superoxide radicals into hydrogen peroxide and water, playing a principal role in the defense against excess Mn in tolerant plants (Sharma et al, 2012;Silva et al, 2017). Meanwhile, POD increased in the shoots of all cultivars.…”
Section: Discussionmentioning
confidence: 96%
“…Yield responses of Macrotyloma axillare (family Fabaceae) to combinations of doses of phosphorus and calcium RENGEL, 2010;SILVA et al, 2017). This is due to the fact that manganese is rapidly transported to the branches, causing, among other symptoms, necrotic scores between the new leaf veins, leaf chlorosis, wilting and poor formation of leaf limbs (LAVRES JUNIOR et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The production of dry biomass of roots increased with the supply of doses of phosphorus (Figure 4b). acceptors, causing the concentration of soluble manganese to increase beyond the levels accepted by the plants, which may result in crop toxicity (KHABAZ-SABERI;RENGEL, 2010;SILVA et al, 2017). This is due to the fact that manganese is rapidly transported to the branches, causing, among other symptoms, necrotic scores between the new leaf veins, leaf chlorosis, wilting and poor formation of leaf limbs (LAVRES JUNIOR et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The yield of Dering I decrease in line with the increasing availability of Mn in the soil. Silva et al (2017) reported that Mn poison in maize may reduce chlorophyll content, plant biomass and plant antioxidants.…”
Section: Copyright © 2019 Universitas Sebelas Maretmentioning
confidence: 99%